Report of 2 Pediatric Cases With Li-Fraumeni Syndrome Related Malignancy in a Family. Issue 4 (May 2021) - Takeoka, Mami; Toyoda, Hidemi; Hirayama, Junya; Suzuki, Naofumi; Hanaki, Ryo; Amano, Keishiro; Iwamoto, Shotaro; Hirayama, Masahiro
Abstract : Li-Fraumeni syndrome (LFS) is a rare inherited disease characterized by a high and early-onset cancer risk. A cancer surveillance program is important to reduce cancer-related morbidity and mortality in individuals with LFS. We report 2 pediatric cases with LFS-related malignancy in a family. Eight-year-old elder brother was diagnosed with adrenocortical carcinoma and was found to have a heterozygous missense germline mutation c.736A>G: p.Met246Val in the TP53 gene. Cancer screening led to the diagnosis of rhabdomyosarcoma at a curable stage in his 2-year-old younger brother. Comprehensive surveillance resulted in early tumor detection and improved survival.